2011
DOI: 10.1055/s-0031-1296724
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Plasma Concentration by Selective Deuteration of Rofecoxib in Rats

Abstract: The plasma concentrations of BDD-11602 (4-[4- (methanesulfonyl)phenyl]-3-(pentadeuterophenyl)-5H-furan-2-one), a rofecoxib derivative in which the positions 2',3;4',5' and 6' of the phenyl ring were deuterated, and rofecoxib (4-(4-methylsulfonylphenyl)-3-phenyl-5H-furan-2-one, CAS 162011-90-7) were compared in order to explore the effects of selective deuteration on the systemic availability. The COX-2 selectivity in vitro was also compared. Following oral gavage administration of 0.1, 1 or 10 mg/kg BDD-11602 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A range of different competing effects might mask or even reverse the consequences of deuteration, such as different rate-limiting steps in enzyme mechanisms, alternative metabolic routes, or competing nonmetabolic elimination mechanisms rendering the translation of in vitro results to in vivo challenging and highly unpredictable. The case of rofecoxib exemplifies this unpredictability . Indeed, d 5 -rofecoxib ( 9 , Figure ) showed a C max of 4181 μg/L compared to a C max of 2416 μg/L for the nondeuterated compound in male rats after 10 mg/kg dose (po), but the two isotopologs exhibited identical half-life values (4.29 h versus 4.18 h).…”
Section: Deuteration and Drug Metabolismmentioning
confidence: 93%
“…A range of different competing effects might mask or even reverse the consequences of deuteration, such as different rate-limiting steps in enzyme mechanisms, alternative metabolic routes, or competing nonmetabolic elimination mechanisms rendering the translation of in vitro results to in vivo challenging and highly unpredictable. The case of rofecoxib exemplifies this unpredictability . Indeed, d 5 -rofecoxib ( 9 , Figure ) showed a C max of 4181 μg/L compared to a C max of 2416 μg/L for the nondeuterated compound in male rats after 10 mg/kg dose (po), but the two isotopologs exhibited identical half-life values (4.29 h versus 4.18 h).…”
Section: Deuteration and Drug Metabolismmentioning
confidence: 93%
“…Improved PK in rats has been reported for 8, a deuterated analog of rofecoxib [40]. The activities of rofecoxib and 8 for inhibition of cyclooxygenase-1 (COX1) in human platelets were assessed and showed similar IC 50 values of 169 and 173 nM, respectively.…”
Section: Deuterated Rofecoxibmentioning
confidence: 97%
“…The effect was attributed to decreased metabolism of p-tyramine by monoamine oxidases. Several reports that have examined the effect of deuteration on the pharmacokinetic and pharmacodynamic properties of drugs reveal results that include little to no effect (Tanabe et al, 1970;Farmer et al, 1979;Taylor et al, 1983;Burm et al, 1988;Dunsaed et al, 1995); increased systemic exposure, a pharmacodynamic effect, and receptor selectivity (Dyck et al, 1988;Schneider et al, 2006Schneider et al, , 2007; and decreased toxicity (Najjar et al, 1978). However, in these studies the mechanisms underlying the observed effects or lack thereof were not examined.…”
Section: Introductionmentioning
confidence: 99%